2013
DOI: 10.3109/09513590.2012.743010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antiproliferative effects of metformine and progesterone on estrogen-induced endometrial hyperplasia in rats

Abstract: Metformin has been shown to inhibit the growth of endometriotic implants, and reverse endometrial hyperplasia when combined with oral contraceptive in a case report. The aim of this study is to compare the antiproliferative effects of medroxyprogesterone acetate (MPA), and metformin in oopherectomized rat endometrium. Forty oopherectomized Wistar-Albino rats were used, and assigned to receive saline, 17 β Estradiol hemihydrate (4 mg/kg), 17 β Estradiol hemihydrate (4 mg/kg) and metformin (50 mg/kg), 17 β Estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…27 It is caused by chronic or repeated progesterone stimulation associated with estrogen priming after repeated estrous cycles without pregnancy. 27 In rats, endometrial hyperplasia can be induced by administration of estrogen, 28 and in rodents, it can also be induced by zearalenone secreted by fungi in contaminated food. 27 In human patients, endometrial hyperplasia is treated by the administration of GnRH agonists.…”
Section: Small Animals and Exoticmentioning
confidence: 99%
“…27 It is caused by chronic or repeated progesterone stimulation associated with estrogen priming after repeated estrous cycles without pregnancy. 27 In rats, endometrial hyperplasia can be induced by administration of estrogen, 28 and in rodents, it can also be induced by zearalenone secreted by fungi in contaminated food. 27 In human patients, endometrial hyperplasia is treated by the administration of GnRH agonists.…”
Section: Small Animals and Exoticmentioning
confidence: 99%
“…In women with PCOS, the endometrium tends to remain in an estrogen-mediated proliferative state due to chronic anovulation and this results in persistent progesterone deficiency [22,42]. Progesterone and its analogs suppress the proliferation and survival of endometrial EC cells [2], and several animal studies have demonstrated that treatment with metformin has a similar effect as progesterone by reducing epithelial cell height, reducing endometrial gland density and thickness under normal conditions [45,46], and inhibiting endometrial cell proliferation under estrogen-regulatory and diabetic conditions [47,48]. …”
Section: Reviewmentioning
confidence: 99%
“…For example, in an animal study [22], Metformin reversed estrogeninduced endometrial hyperplasia in mice. Studies have also shown that insulin and insulin-like growth factors (IGFs) are thought to be the precursors in carcinogenesis, including reports of an exaggeration of insulin receptors in endometrial cancer [9,23].…”
Section: Discussionmentioning
confidence: 99%